Evaluasi User Experience Pada Aplikasi Mobile Penjualan Tiket Online - Rizky Ashar Murdiono; Herman Tolle; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The application of mobile ticketing is a breakthrough from the transport and e-commerce agencies to facilitate the access of transportation users who want to make transactions without having to come to the ticket service. In the use of mobile-ticketing applications, some applications do not use the appropriate tools, such as the features offered are not functioning properly, additional information such as airport taxes, and goods information is not present in some mobile-ticketing applications, it is a consideration for users. On subjective evaluation, the value of usefulness, usability, and desireability parameters is accumulated, from the accumulated result Mobile-Ticketing Traveloka has the highest value compared to Tiket.com. Based on the objective evaluation result of the parameters of task completed and error during task performance, it can be concluded that both applications have been effective application mobile-ticketing, all tasks run well. For an efficient level, the global value of geo mean parameters of time per completed task and number of clicks during task completion is accumulated. Based on the evaluation result, Traveloka mobile-ticketing application has the shortest time and sufficient number of clicks, so it can be concluded that Traveloka mobile ticketing application is more efficient to use compared to ticket.com application.